2017
DOI: 10.5897/ijbc2017.1085
|View full text |Cite
|
Sign up to set email alerts
|

Structure and regeneration status of woody plants in the Hallideghie wildlife reserve, North East Ethiopia

Abstract: In this study, we examined vegetation structure and regeneration status of woody plants in the Hallideghie wildlife reserve, Ethiopia. We collected data on abundance, height and diameter at breast height (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(17 reference statements)
2
4
1
Order By: Relevance
“…This might be associated with the selective cutting of species for fuel wood collection, local house building (hat house), charcoal production and others. Similar results were observed in [21] [42] [43] [44] [45].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This might be associated with the selective cutting of species for fuel wood collection, local house building (hat house), charcoal production and others. Similar results were observed in [21] [42] [43] [44] [45].…”
Section: Discussionsupporting
confidence: 92%
“…This might be species are harvested at an early growth stage by the local people for charcoal production, live fence and construction of houses. Several studies were reported in the different region of Ethiopia for [46] in the Sheko forest; [43] in the Hallideghie wildlife reserve; [47] Vegetation Ecosystem of Ethiopia; [44] in the boda dry evergreen Montana forest; [48] in the rangeland of Southeast Ethiopia and [49] in the Kimphe Forest.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S. persica and C. rotundifolia under non-invaded woodlands showed good regeneration in the study areas. In contrast to our findings, the findings of Endris et al [52] showed that P. juliflora under P. juliflora mixed with native species stands and A. mellifera under non-invaded woodlands showed good regeneration profiles in the Hallideghie wildlife reserve, Northeast Ethiopia. Furthermore, the density of seedlings for P. juliflora and A. tortilis under P. juliflora mixed with native species stands, non-invaded woodlands, and P. juliflora thicket also showed inconsistent patterns of densities in comparison to reports by Muturi et al [29] that show higher densities in comparison to trees and saplings.…”
Section: P Juliflora Invasion Levels and Size Class Structures Of Secontrasting
confidence: 99%
“…We also found that Shannon diversity index was more drastically decreased in the SP forest than the MP and BP forests and such traits are common patterns found in forest areas affected by human activity. The results are consistent with previous reports, such as Endris et al (2017); Kacholi (2014) that increasing tree size classes results in a drastically decreased number of species and Shannon diversity index. Basal area and AGC were increased from smaller to bigger size classes in the BP and MP forests (Goode et al 2020).…”
Section: Size Class Distributionsupporting
confidence: 93%